Cell survival prediction in hadrontherapy with the NanOx biophysical model - Alcocer-Ávila, Mario; Monini, Caterina; Cunha, Micaela; Testa, Étienne; Beuve, Michaël (Frontiers in Physics, 2022)
Biophysical models are useful tools for predicting the biological effects of ionizing radiation. From a practical point of view, these models can help clinicians optimize the radiation dose delivered to patients in particle therapy. The biophysical model NanOx was recently developed to predict cell survival fractions in the context of radiotherapy. The model takes into account the stochastic nature of radiation at different levels and considers as well the accumulation of radio-induced oxidative stress in cells caused by reactive chemical species. We show in this work how the general formalism of NanOx is adapted to hadrontherapy applications. We then use NanOx to compute the cell survival fractions for three cell lines (V79, CHO-K1 and HSG) in response to carbon ions of different energies, and benchmark the predictions against experimental data. The results attest that NanOx provides a good description of both the overkill effect and the evolution of the shoulders of cell survival curves with linear energy transfer.